Kelayakan Usaha Tani Cabai Merah Pada Lahan Sawah Dan Pasir Di Kabupaten Bantul - Meisya Nurcahyani; Lestari Rahayu Waluyati; Agus Dwi Nugroho (Universitas Wahid Hasyim, 2025)
Red chili is a horticultural commodity with high economic value and can be planted in various land conditions. This study was conducted on red chili farming in rice fields and sandy land in Bantul Regency. The purpose of this study was to determine the characteristics of red chili farming production factors used in rice fields and sandy land, to determine the comparison of revenue, costs, income, and profits of red chili farming in rice fields and sandy land, and to assess the feasibility of red chili farming in rice fields and sandy land. The study location was determined by purposive sampling, considering that Kapanewon Kretek and Sanden are the leading producers of red chili in Bantul Regency. The total respondents in this study were 30 farmers in each study area. R/C ratio analysis and π/C ratio were used as the analysis model. The results showed that the use of manure and machine were significantly different in red chili farming in rice fields and sandy land, while the use of labor, seeds, phonska fertilizer, NPK, ZA, and KCL production factors was not significantly different. There are no significant differences in income, costs, revenues, and profits of red chili farming in rice fields and sandy land. Red chili farming activities are feasible to be conducted in both areas. Keywords: red chili, feasibility, rice fields, sandy land, farming